The Impact of Incentive Systems on Employee Performance:The Mediating Role of ‎Transformational Leadership in Oman’s Banking Sector - Al Bulushi , Mohammed Murad Mohammed; Tharikh , Shafazawana Mohamed; Al Busaidi , Z. A. (International Journal of Accounting and Economics Studies, 2025)
Incentive systems are among the most strategic human resource mechanisms used to enhance employee ‎motivation and organisational performance. However, the behavioural processes through which incentives ‎lead to improved performance outcomes remain underexplored, particularly in developing economies. This ‎study examines the mediating role of transformational leadership in the relationship between incentive ‎systems and employee performance in Oman’s banking sector. Grounded in the Resource-Based View ‎‎(RBV) and Transformational Leadership Theory, the study proposes that well-designed incentive systems ‎promote transformational leadership behaviours, thereby enhancing employee motivation, engagement, and ‎performance. Data were collected from 346 non-managerial employees of the Central Bank of Oman ‎‎(CBO) using a structured questionnaire. Partial Least Squares Structural Equation Modeling (PLS-SEM) ‎was applied to test the hypothesised model. The results show that incentive systems have a significant ‎positive effect on both transformational leadership and employee performance. Moreover, transformational ‎leadership partially mediates this relationship, suggesting that incentives not only motivate employees ‎extrinsically but also cultivate leadership behaviours that strengthen intrinsic motivation and collective ‎achievement. The study contributes to strategic human resource management (SHRM) theory by identifying ‎leadership behaviour as a key mechanism linking HR systems to performance outcomes, and it provides ‎practical insights for Omani banks to design incentive frameworks that reinforce leadership-driven ‎excellence‎.